Identification of a T1D Susceptibility Gene - Grant Morahan (The Scientific World Journal)
It is not known what causes type 1 diabetes (T1D), which affects over 1 million people in the U.S. alone. Each year, 30,000 young people in the U.S. develop this disease and depend on insulin injections thereafter. Because of the huge cost to the individual, the family, and to society in increased health care costs, it is important to find what makes these people susceptible. The disease process itself is clear: the individual’s immune system — T lymphocytes in particular — attack and destroy the body’s insulin-producing cells. But how and why this autoimmune process starts or proceeds unregulated is still not known.